Hubungan Antara Body Shaming Dan Kecemasan Sosial Pada Siswa SMA Harapan 3 - Mery Christine Lumban Gaol; Sabrini Mentari Rezeki; Siti Rahma Aura; Ade Intan Felicia Sianturi; Achmad Irvan Dwi Putra; Lusinta Rehna Ginting; Nurvica Sary (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between body shaming and social anxiety in students of SMA Harapan 3. This study uses a quantitative method with a correlational design. For data collection, the disproportionate stratified random sampling technique was used. This study used a population of 140 students with a sample of 100 respondents. The research instrument used includes two scales, namely the anxiety scale with 31 statements and a reliability of 0.753 and the body shaming scale with 24 statements and a reliability of 0.757. The results of the study found that the higher the body shaming, the higher the anxiety experienced by students. With a product moment value of 0.778 with a significance value (p) of 0.000 (p < 0.05). This indicates a positive relationship between the two variables with a significant level of relationship which is included in the fairly strong category.